Treatment of protruding osseo integrated dental implant - Buddula Aravind; Sheridan Phillip; Balshe Ayman (Wolters Kluwer Medknow Publications, 2010)
Titanium dental implants have been used in the treatment of partial or complete edentulism. The height and width of the residual alveolus and surrounding anatomical structures can determine the proper position and path of insertion of dental implants. The following case report describes the treatment of a malpositioned osseo integrated dental implant with an apex perforating the buccal cortex of alveolar bone. A 61-year-old male was referred by his local dentist for the chief complaint of a swelling at site of tooth 14 where an implant was present. Intraoral clinical examination revealed an implant supported porcelain fused to metal crown replacing the maxillary right first premolar. A peri-apical radiograph of the implant revealed no signs of peri-implant bone loss or radiolucency. Surgical exploration and modification of the protruding implant. The area healed uneventfully without the need of explantation of the implant in site of tooth 14. We felt that the conservative treatment provided was prudent and treatment of choice and anticipate that the implant will most likely continue to function for a lifetime.